Reconstruction of the forehead acoustic properties in an IndoPacific humpback dolphin (Sousa chinensis), with investigation on the responses of soft tissue sound velocity to temperature - Song, Zhongchang; Zhang, Yu; Berggren, Per; Wei, Chong (ACOUSTICAL SOC AMER AMER INST PHYSICS, 2017)
Computed tomography (CT) imaging and ultrasound experimental measurements were combined to reconstruct the acoustic properties (density, velocity, and impedance) of the head from a deceased Indo-Pacific humpback dolphin (Sousa chinensis). The authors extracted 42 soft forehead tissue samples to estimate the sound velocity and density properties at room temperature, 25.0  °C. Hounsfield Units (HUs) of the samples were read from CT scans. Linear relationships between the tissues' HUs and velocity, and HUs and density were revealed through regression analyses. The distributions of the head acoustic properties at axial, coronal, and sagittal cross sections were reconstructed, suggesting that the forehead soft tissues were characterized by low-velocity in the melon, high-velocity in the muscle and connective tissues. Further, the sound velocities of melon, muscle, and connective tissue pieces were measured under different temperatures to investigate tissues' velocity response to temperature. The results demonstrated nonlinear relationships between tissues' sound velocity and temperature. This study represents a first attempt to provide general information on acoustic properties of this species. The results could provide meaningful information for understanding the species' bioacoustic characteristics and for further investigation on sound beam formation of the dolphin.